Findings related to rotational malalignment in tibial fractures treated with reamed intramedullary nailing - Say, Ferhat; Bülbül, Murat (Springer, 2014)
Introduction: Rotational malalignment following closed intramedullary nailing of tibial fractures does not attract attention but is a complication which may lead to serious results. This study aimed to present findings related to rotational malalignment from rotational alignment measurements made clinically and with computerised tomography (CT) in patients who had undergone locked intramedullary nailing for tibial fracture.Materials and methods: A total of 26 patients (male/female: 23/3) were evaluated after application of reamed locking intramedullary nailing to a diagnosed tibial shaft fracture. The mean age was determined as 37.5 ± 15.6 years. Rotational alignment was measured in both lower extremities clinically as thigh-foot angle (TFA) and radiologically with CT. Rotational malalignment was accepted as a more than 10º difference between the two lower extremities.Results: Malrotation was determined at more than 10º from TFA in two (7 %) of 26 patients and from CT in five (19 %) of 26 patients. In three of them, the malrotation was >15º. Of the patients determined with malrotation with CT, it was determined from clinical measurements in 40 %. The mean rotational difference was determined as greater with CT measurement (4.7° ± 9.5) compared to the TFA (1.1° ± 5.6) (p < 0.001). No statistically significant relationship was determined between a rotational difference over 10º and the AO fracture type, fracture location and fibula fixation.Conclusions: A significant number of patients treated with intramedullary nailing for a tibial fracture may result in rotational malalignment. To determine rotational malalignment, a thorough clinical evaluation must be made and different kinds of clinical measurements taken and, when suspicions remain, determination should be made by CT.
Keywords: Computerised Tomography; Intramedullary Nail; Malrotation; Tibia